2020
DOI: 10.1136/bmjopen-2019-036503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a mass media campaign on breast cancer symptoms awareness and screening uptake in Malaysia: findings from a quasi-experimental study

Abstract: ObjectiveTo evaluate the impact of a mass media campaign in terms of improving breast cancer (BC) symptoms awareness and screening uptake.DesignBefore—and after—study with comparator groups.SettingSelangor State, Malaysia.ParticipantsMalaysian women aged >40 years (n=676) from randomly selected households.InterventionA culturally adapted mass media campaign (TV, radio, print media and social media).Primary and secondary outcome measuresThe primary endpoint was BC symptoms awareness, which was assessed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…We have reported nation-wide awareness levels for the following cancer symptoms: 'lump' -74.5%, rectal bleeding -65.5% and 'persistent cough' -55.4% [8] whereas other (albeit smaller) studies reported proportions ranging from 28% to 91% for awareness of lump as a breast cancer symptom [9][10][11] and between 34% and 72% for rectal bleeding as a colorectal cancer sign [12][13][14]. Awareness about lung cancer symptoms is largely unexplored [15].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We have reported nation-wide awareness levels for the following cancer symptoms: 'lump' -74.5%, rectal bleeding -65.5% and 'persistent cough' -55.4% [8] whereas other (albeit smaller) studies reported proportions ranging from 28% to 91% for awareness of lump as a breast cancer symptom [9][10][11] and between 34% and 72% for rectal bleeding as a colorectal cancer sign [12][13][14]. Awareness about lung cancer symptoms is largely unexplored [15].…”
Section: Introductionmentioning
confidence: 70%
“…In Malaysia, breast, colorectal and lung cancer are the most common cancers (ASR 34.1/100,000, 25.9/100,00 and 19.1/100,000 respectively) [3]. About 50% of breast cancer cases, over 70% of colorectal cancer cases and over 90% of lung cancer cases are diagnosed at stage 3 or 4; and contribute to increasing cancer mortality (9,466 in 2012 vs 11,966 in 2016) [3]. In addition, there were 5,257 non-medically certified cancer deaths in 2012 and 6,731 in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…These four items included emotion-related barriers, such as fear of finding out that something (about their breast health) was wrong, fear of attending screening because of their limited understanding about what they would be required to do, and a lack of encouragement and support from relatives to attend the screening, and a service-related barrier about not knowing how to access and use screening. In a related report, 40% of respondents stated that they discussed the BCAC-BC campaign with friends and family and 21.7% reported that they or their family or friends visited a doctor after seeing the campaign advertisement [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although some randomized control trials have been conducted, 120 , 142 the majority of early diagnosis programs are natural experiments and so evaluations more often take other forms such as before and after designs and interrupted time series analysis, commonly involving mixed-methods research. 22 , 25 , 27 , 40 , 135 , 143 - 145 …”
Section: Monitoring and Evaluationmentioning
confidence: 99%
“…The campaign's logic model takes contextual factors into account, including differences in knowledge and cultural norms between the main ethnic groups in Malaysia (Malays, Chinese, and Indian) and health and media literacy. 27 Recently published findings indicate improvements in symptom awareness at follow-up across ethnic and social strata although, in common with the English experience, evidence of improvements in downstream outcomes was less clear. 28 …”
Section: Introductionmentioning
confidence: 99%